Children's and Parents' Evaluations of 'FRIENDS for Life', an Indicated School-Based Prevention Program for Children With Symptoms of Anxiety and Depression. Issue 4 (18th September 2015) - Zwaanswijk, Marieke; Kösters, Mia P.
Abstract : There is evidence that the school-based program FRIENDS for Life is effective in preventing childhood anxiety and depression. Effectiveness is, however, not the only prerequisite for successful implementation. Participants' evaluation of a prevention program may provide suggestions about how to fine-tune it to fit the needs of the target population. This study investigated children's and parents' evaluations of the Dutch version of FRIENDS for Life. Forty-four participants of FRIENDS for Life (9–13 years) participated in online focus groups and 38 parents were interviewed in 2011–2012. Questions concerned the general opinion about the program, its perceived effectiveness and group atmosphere, and suggestions for program improvement. Most children (95.5%) and parents (65.8%) evaluated the program positively, and the majority (61.4% and 76.3%) thought that it had been useful in changing the child's behaviour. Children and parents expressed complementary views about the behaviours the child had learned. Some children (38.6%) expressed negative opinions about the program. Parents' attendance at parent meetings was low (31.6–36.8%). Considered together with the growing evidence of the effectiveness of FRIENDS for Life, we concluded that it can be successfully implemented as an indicated prevention program in primary schools for children who show symptoms of anxiety or depression. Efforts could be made to increase parents' involvement in the program.